Prioritization of the human health and safety loss factor subject to offshore pipeline accidents - Maziah Munirah, M S; Libriati, Z; Nordin, Y; Norhazilan, M N (IOP conference series. Earth and environmental science, 2019)
Accidents at the offshore platform are unavoidable due to unexpected reasons. The nature of its operations involves unstable materials sometimes under extreme pressure in aggressive environments lead to increase in risk thus accidents and tragedies can cause higher severity to platform's workers. Risk assessment in oil and gas (O&G) industry are essential to protect human and ecosystem from damages as it helps to create awareness and identify if existing control measure are adequate enough or vice versa for hazards and risks before accident happens. Consequence of failure (CoF) is a part of risk assessment process consists of four categories which are people loss, asset loss, environmental loss and reputation loss. In the current standard using by O&G industry in Malaysia which is PETRONAS Technical Guideline (PTG), CoF are being generally classified as incomprehensive because it does not consider many factors. Identifying more factors leads to better risk assessment as it helps in reducing unnecessary inspection or maintenance that could lead to excessive allocation of money for risk assessment. The objective of the study is to identify human health and safety loss threat factors. This study focuses on CoF of people loss or also known as human health and safety loss for offshore platform facilities damages. The information and identification of parameters related to human health and safety loss of offshore platform facilities damage are determined from case studies and literature review. All the information gathered are then being verified by O&G PETRONAS experts through survey and interviews. As a result, it is determined that the threat factors for human health and safety loss are fatality, injuries, disabilities and illness. In conclusion, identification of these threat factors as agreed by experts is more realistic as the severity levels of the accident are unique thus the factors should be more various.